DSM-5 Overview of DSM-4 Changes. (BarCharts, Inc., 2014)
Easily accessible overview of highly relevant changes from the fourth edition to the fifth edition of the Diagnostic and Statistical Manual of Mental Health Disorders (DSM) handbook used by health care professionals as a guide to diagnosing mental disorders. Changes and disorders are summarized for quick reference for use by students and/or professionals in the field. Topics summarized include: *Structural and Organizational Revisions *Changes in Terminology *Neurodevelopment Disorders *Schizophrenia Spectrum and Other Psychotic Disorders *Bipolar and Related Disorders *Depressive Disorders *Obsessive Compulsive and Related Disorders *Anxiety Disorders *Trauma and Stressor Related Disorders *Dissociative Disorders *Somatic Symptom and Related Disorders *Feeding and Eating Disorders *Sleep-Wake Disorders *Sexual Dysfunctions *Disruptive, Impulse-Control, and Conduct Disorders *Substance Abuse and Addictive Disorders *Neurocognitive Disorders *Personality Disorders *Paraphilic Disorders. --Provided by publisher.